Nilai-nilai Islam pada Tradisi Selametan Masyarakat di Desa Sempu - Sa’uud Taufiqurahman Suwandi; Dewi Yunita Sari (Social Science Academic, 2025)
The tradition of selametan is one of the local wisdoms of the Javanese people that still survives to this day, including in Sempu Village, Ngebel District, Ponorogo. This study aims to explain the Islamic and cultural values contained in the selametan tradition and its role as a contextual medium for da'wah. Using the Asset-Based Community Development (ABCD) approach and qualitative methods through observation, interviews, and documentation, the study found that selametan not only functions as a ritual of prayer and gratitude, but also as an effective means of spreading Islamic teachings through culture. The symbols of offerings in selametan contain the philosophy of piety, self-awareness, and human relationships with God, nature, and each other. This tradition also strengthens ukhuwah (brotherhood), social solidarity, and maintains harmony within the community. Thus, selametan plays an important role in preserving Javanese culture while strengthening Islamic da'wah in the modern era.